Legal Determinants of Health: Historic Housing Policy and Modern Day Surgical Outcomes. (15th September 2021) - Diaz, Adrian; O'Reggion, Rachel; Norman, Marc; Thumma, Jyothi; Dimick, Justin; Ibrahim, Andrew
Abstract : Research Objective: In 1933 the United States Government Home Owners Loan Corporation used racial composition of neighborhoods to determine creditworthiness and labeled them "Best", "Still Desirable", "Definitely Declining" and "Hazardous." Although efforts have been made to reverse these racist policies that structurally disadvantage Black Americans, the lasting legacy on modern day healthcare outcomes is uncertain. The objective of this study was to evaluate the association of historical racist housing policies and modern day healthcare outcomes. Study Design: Cross‐sectional retrospective review of Medicare beneficiaries' who underwent one of five of common surgical procedures across neighborhoods historically labeled by the Home Owners Loan Corporation. Outcomes were risk‐adjusted using a multivariable logistical regression model accounting forpatient factors (age, sex, Elixhauser comorbidities), admission type (elective, urgent, emergency), and type of operation. Population Studied: 525, 690 Medicare beneficiaries' admissions between 2012 and 2016 who underwent one of five of common surgical procedures ‐ coronary artery bypass, appendectomy, colectomy, cholecystectomy and hernia repair – across neighborhoods historically labeled by the Home Owners Loan Corporation. Principal Findings: Overall, 473, 732 Medicare beneficiaries (mean age, 74.6 years; 49.8% women) underwent 520, 690 operations within neighborhoods that had been historically graded by the Home Owners Loan Corporation. Mortality increased in a stepwise fashion across neighborhoods. Overall, 30‐day postoperative mortality was 4.3% in "Best" neighborhoods, 4.7% in "Still Desirable", 4.8% in "Definitely Declining" and 5.1% in "Hazardous" (Best vs. Hazardous Odds Ratio = 1.21 [1.16–1.26]; P < 0.001). The same stepwise increase was present for each procedure individually across the following ranges: coronary artery bypass (2.8% to 3.3%), appendectomy (2.8% to 3.3%), colectomy (8.0% to 9.3%), cholecystectomy (3.1% to 3.7%) and hernia repair (3.7% to 4.4%). Mortality rates also increased significantly in a stepwise manner across neighborhoods for White (4.6% to 5.2%, p < 0.001) and Black (5.3% to 6.0%, p = 0.002) racial groups. Black Medicare Beneficiaries had higher mortality rates compared to non‐Blacks overall (5.8% vs 5.0%; absolute difference + 0.8%) with persistent disparity across neighborhoods from 5.3% vs 4.6% (+0.7%) in "Best" neighborhoods to 6.0% vs 5.2% (+0.8%) in "Hazardous" neighborhoods. Conclusions: Discriminatory housing policy was associated with increasing rates of post‐operative mortality across neighborhoods for all racial groups, with Black Medicare beneficiaries being disproportionately affected. Implications for Policy or Practice: These findings underscore the long term sequelae of housing policies and raise concern about policies that reward or penalize hospitals based on their outcomes without taking into account possible structural disadvantages within certain communities. Primary Funding Source: National Institutes of Health.